Implementation of the modified V-Notched Rail Shear method for characterizing glass fibre thermoplastic composites at sub-zero and elevated temperatures - Antoniomaria Di Ilio (Elsevier, 2021)
In the recent years, the thermoplastic-based composites are being increasingly used in a variety of industrial applications such as the automotive due to the unique features they exhibit, mainly their recyclability and their interesting capacity to be formed and produced in high volume rate. Among the most interesting categories utilized extensively in these sectors, the short fibre composites are an attractive solution to non-critical load carrying structures while the textiles are utilized in more critical components. Nevertheless, all of them are implemented into a varying service temperature range, from sub-zero up to higher temperatures than the ambient. Thus, the definition of their mechanical performance with respect to their material and fabrication characteristics is a crucial procedure. Among them, the shear properties are the most challenging due to the complexity of the standardized mechanical tests. Moreover, these properties are greatly dependent on the matrix quality and, in general, to the overall composite's quality. In the present work, presented is an experimental campaign implementing temperatures from −30 °C up to 80 °C that includes both short and textile thermoplastic based composites, fabricated with different processes. In addition, introduced is a modified testing apparatus based on the standardized one that aims to overcome some of the drawbacks observed so far.